A STUDY ON CUSTOMER SATISFACTION TOWARDS SAKTHI MASALA PRODUCTS IN SALEM DISTRICT - Rajamanickam (International Journal of Research -GRANTHAALAYAH, 2016)
SAKTHI MASALA” the Queen of spices as the household name among the millions today, it was doing Turmeric trading for some time. Later entered into the arena of pure spice powders like Turmeric, Chilli and Coriander. This inquisitiveness lets to enter into masala world with boldness. This masala encountered a lot of hurdles, since selling masala powders during those days to the oriental women who are traditionally conservative; it was not easy to sell. It was concept sealing on “Easy Cooking” rather than marketing food products with self-determination and persistent attempts it was able to get into the kitchens of our country and the rest of the world. The store may look like a miracle, but the hard work, the pot holes and the bumps on the way and the stormy inclement weather are known only to producer. The person who stood behind produce masala for all those achievement was with help of their business partner.